2007
DOI: 10.1111/j.1365-2613.2007.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor (VEGF), VEGF receptors expression and microvascular density in benign and malignant thyroid diseases

Abstract: Angiogenesis is critical for the growth and metastatic spread of tumours. Vascular endothelial growth factor (VEGF) is the most potent inducer of neovasculature, and its increased expression has been related to a worse clinical outcome in many diseases. The purpose of this study was to evaluate the relation between VEGF, its receptors (VEGFR-1 and VEGFR-2) and microvessel density (MVD) in thyroid diseases. Immunostaining for VEGF and VEGF receptors was performed in 66 specimens of thyroid tissue, comprising 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 47 publications
5
72
0
2
Order By: Relevance
“…This finding is relevant because higher expression of VEGF-A is often associated with tumour growth due to his potential contribution for providing nutrients for cell proliferation. In agreement with other articles in the literature, our study demonstrates that the levels of immunoexpression of VEGF-A in morphologically normal adjacent regions is lower than that found in the papillary and follicular neoplasms of the thyroid [21]. We demonstrate that almost 100% of papillary and follicular carcinomas showed immunohistochemical positive expression of VEGF-A in cancer cells.…”
Section: Discussionsupporting
confidence: 79%
“…This finding is relevant because higher expression of VEGF-A is often associated with tumour growth due to his potential contribution for providing nutrients for cell proliferation. In agreement with other articles in the literature, our study demonstrates that the levels of immunoexpression of VEGF-A in morphologically normal adjacent regions is lower than that found in the papillary and follicular neoplasms of the thyroid [21]. We demonstrate that almost 100% of papillary and follicular carcinomas showed immunohistochemical positive expression of VEGF-A in cancer cells.…”
Section: Discussionsupporting
confidence: 79%
“…The current authors hypothesize that the observed overlap in CEUS perfusion was a result of the specific tissue biostructures of the investigated nodules. Jebreel et al (22) reported that differences in the microvessel density of benign lesions measuring <1 cm in diameter and malignant nodules may not be evident when the tumors are small. Furthermore, small malignant nodules may not exhibit typical characteristics of malignant tumors, including a large variation in vascular diameter and shape, a large number of vascular branches, easy formation of arteriovenous fistulae, low efficiency of new tumor vessels, or edema and fibrosis of the lesion stroma (22).…”
Section: Discussionmentioning
confidence: 99%
“…In phase III studies, reported rates have ranged from 4% to 16% (4, 7), and in a rare prospective observational study, 27% of patients treated with sunitinib developed sub-or clinical hypothyroidism requiring hormone replacement (28). The mechanisms by which sunitinib affects thyroid function remain unclear but may include antiangiogenic effects (29,30), iodine uptake inhibition (31), destructive thyroiditis (32), inhibition of thyroid peroxidase activity (33), and reduction of vascularity (34) by capillary regression and/or constriction.…”
Section: Molecular Basis Of Hypothyroidismmentioning
confidence: 99%
“…The antiangiogenic effect of sunitinib may be responsible for capillary regression (29,34) that enhances toxicity to the thyroid gland. In normal thyroid follicular cells, thyroid-stimulating hormone or thyrotropin (TSH) induces the expression of VEGF and VEGFR, thereby influencing angiogenesis (35).…”
Section: Molecular Basis Of Hypothyroidismmentioning
confidence: 99%